Board monitoring and covenant restrictiveness in private debt contracts during the global financial crisis - Abu Bakar, Intan Suryani; Khan, Arifur; Mather, Paul R.; Tanewski, George A. (Blackwell Publishing, 2020)
We examine the association between board independence and restrictiveness of covenants in U.S. private debt contracts around the global financial crisis (GFC). We show that board independence is associated with less restrictive covenants suggesting lenders willingness to delegate some monitoring of firms with independent boards. More nuanced analysis between the pre-GFC, GFC and post-GFC periods shows mixed results and we suggest that, during the GFC and its aftermath, lenders place more emphasis on ex ante screening relative to ex post monitoring. We contribute to the literature by providing evidence on covenant use and lenders choices in periods of credit rationing. © 2018 AFAANZ